Treatment of Epithelioid Sarcoma at the Royal Marsden Hospital. (2003) - Livi, L.; Shah, N.; Paiar, F.; Fisher, C.; Judson, I.; Moskovic, E.; Thomas, M.; Harmer, C.
Abstract : Purpose: The aim of this study was to assess treatment and outcome with respect to clinical and pathological features. Patients and methods: Thirty-nine patients were identified (range 7–66 years, mean 23). Initial treatment comprised local excision in 11 patients and wide excision in 14. Post-operative external beam radiotherapy was prescribed in 22 patients with a total dose of 60 Gy, delivered in two phases. Results: The cause-specific survival for the entire group was 79, 63, 56 and 45% at 1, 3, 5 and 10 years, respectively. A distal limb location was associated with a better prognosis than proximal limb location ( P = 0.04). Conclusions: Our data favour treatment with wide functional excision followed by radical dose radiotherapy in attempt to minimize risk of local recurrence, especially when primary tumours are bigger than 3 cm. Our data also suggest the same treatment for local recurrence, when technically possible, to avoid amputation.